2006
DOI: 10.1159/000096474
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Intravenous Iron on Oxidative Stress in Hemodialysis Patients at Various Levels of Vitamin C

Abstract: Background/Aims: Vitamin C levels decrease during hemodialysis (HD), which deteriorates antioxidant defense. Vitamin C may also act pro-oxidatively, via reduction in Fe(III). We sought to determine whether intravenous iron (Feiv)-induced oxidative stress differs in HD patients with low and physiological vitamin C levels and whether intravenous vitamin C (Civ) administration during HD would change the response to Feiv. Patients and Methods: Twenty patients with vitamin C deficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 60 publications
0
14
0
1
Order By: Relevance
“…1) [7,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58], representing 24 single-arm or cohort studies and 10 parallel-arm RCT; 32 studies (94%) were published in full-text articles and 2 (6%) were scientific abstracts. The characteristics of the individual studies are displayed in table 1.…”
Section: Resultsmentioning
confidence: 99%
“…1) [7,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58], representing 24 single-arm or cohort studies and 10 parallel-arm RCT; 32 studies (94%) were published in full-text articles and 2 (6%) were scientific abstracts. The characteristics of the individual studies are displayed in table 1.…”
Section: Resultsmentioning
confidence: 99%
“…However, an effect of vitamin C on lipid peroxidation cannot be ruled out in this study, because vitamin C not only enhances iron absorption, but can also increase intracellular peroxidation via an iron-dependent reaction [47]. As an anti-oxidant, vitamin C can also affect lipid oxidation dose-dependently [48]. …”
Section: Iron and Oxidative Stressmentioning
confidence: 99%
“…Vitamin C may also act as a pro-oxidant via the reduction of ferric ion. Hemodialysis patients who received 100 mg of iron sucrose and vitamin C intravenously had an increase in oxidative stress comparable to patients given iron alone (Eiselt et al, 2006); however, this finding was not confirmed by Shi et al (2005). This suggests that combination treatment of high doses of iron and vitamin C by intravenously route, should be avoided in anemic hemodialysis patients.…”
Section: Vitaminsmentioning
confidence: 81%